2011
DOI: 10.4137/cmrt.s7398
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Pregabalin for the Treatment of Peripheral and Central Neuropathic Pain and Its Place in the Treatment of Chronic Pain

Abstract: Pregabalin is an α2-δ ligand indicated for the treatment of peripheral and central neuropathic pain. In this article, we will review the pharmacodynamics, pharmacokinetics, randomized clinical trials supporting its efficacy for a wide array of neuropathic painful conditions, and the tolerability of this medication. We will comment the main differences with gabapentin, its parent compound, both from the pharmacological and clinical perspective. Our experience in the clinical practice setting with pregabalin, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 103 publications
(166 reference statements)
1
6
0
Order By: Relevance
“…Relevant improvements in anxiety, depression, subjective sleep quality, and quality of life were observed after treatment with add-on pregabalin. This improvement in other dimensions of neuropathic pain is consistent with what it is known from randomized clinical trials in patients with neuropathic pain [9] and from previous studies on patients with refractory neuropathic pain [12, 14, 17, 40]. …”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Relevant improvements in anxiety, depression, subjective sleep quality, and quality of life were observed after treatment with add-on pregabalin. This improvement in other dimensions of neuropathic pain is consistent with what it is known from randomized clinical trials in patients with neuropathic pain [9] and from previous studies on patients with refractory neuropathic pain [12, 14, 17, 40]. …”
Section: Discussionsupporting
confidence: 89%
“…Whether this higher score reflects a worse clinical condition or a greater neuropathic component of the pain is impossible to answer. Pregabalin has consistently been demonstrated, in several randomized clinical trials, to be effective for the treatment of painful diabetic neuropathy, and in fact is considered a first-line option for the treatment of this condition in most clinical guidelines [9]. Central neuropathic pain is very disabling and difficult to treat, and only a few drugs in a few studies have shown positive results for this condition [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations